Output‐based event‐triggered control of networked systems subject to bilateral packet dropouts. (1st February 2022) - Li, Chengchao; Wu, Chunyu; Abozinadah, E.; Alassafi, Madini O.; Xu, Ning
Abstract : In this paper, an output‐based event‐triggered control problem of discrete‐time networked control systems (NCSs) subject to bilateral packet dropouts is investigated. In view of stochastic sequences of packet dropouts in the measurement channels (from sensors to controller) and the control channels (from controller to actuators), the NCS is converted into a closed‐loop stochastic parameter system. In the aid of a Lyapunov functional based on stochastic variables, the sufficient conditions on design of a dynamic output feedback control law and bilateral event‐triggering conditions are derived to guarantee the exponentially mean‐square stability for NCSs. Furthermore, an improved iterative algorithm is given to obtain the output‐based control law and event‐triggering parameters from a set of nonconvex inequalities. Finally, a numerical example and the corresponding simulation results are given to illustrate the validity and applicability of the developed techniques.